IL-2 and IL-15 drive intrathymic development of distinct periphery-seeding CD4+Foxp3+ regulatory T lymphocytes - Apert, Cécile; Galindo-Albarrán, Ariel O.; Castan, Sarah; Detraves, Claire; Michaud, Héloise; McJannett, Nicola; Haegeman, Bart; Fillatreau, Simon; Malissen, Bernard; Holländer, Georg; Žuklys, Saulius; Santamaria, Jérémy C.; et al. (Frontiers in Immunology, 2022)
Development of Foxp3-expressing regulatory T-lymphocytes (Treg) in the thymus is controlled by signals delivered in T-cell precursors via the TCR, co-stimulatory receptors, and cytokine receptors. In absence of IL-2, IL-15 or their receptors, fewer Treg apparently develop in the thymus. However, it was recently shown that a substantial part of thymic Treg are cells that had recirculated from the periphery back to the thymus, troubling interpretation of these results. We therefore reassessed the involvement of IL-2 and IL-15 in the development of Treg, taking into account Treg-recirculation. At the age of three weeks, when in wt and IL-15-deficient, but not in IL-2-deficient mice substantial amounts of recirculating Treg are present in the thymus, we found similarly reduced proportions of newly developed Treg in absence of IL-2 or IL-15, and in absence of both cytokines even less Treg developed. In neonates, when practically no recirculating Treg were found in the thymus, the absence of IL-2 led to substantially more reduced Treg-development than deficiency in IL-15. IL-2 but not IL-15 modulated the CD25, GITR, OX40, and CD73-phenotypes of the thymus-egress-competent and periphery-seeding Treg-population. Interestingly, IL-2 and IL-15 also modulated the TCR-repertoire expressed by developing Treg. Upon transfer into Treg-less Foxp3sf mice, newly developed Treg from IL-2- (and to a much lesser extent IL-15-) deficient mice suppressed immunopathology less efficiently than wt Treg. Taken together, our results firmly establish important non-redundant quantitative and qualitative roles for IL-2 and, to a lesser extent, IL-15 in intrathymic Treg-development.